A fast radio burst with a low dispersion measure. Issue 3 (27th October 2018) - Petroff, E; Oostrum, L C; Stappers, B W; Bailes, M; Barr, E D; Bates, S; Bhandari, S; Bhat, N D R; Burgay, M; Burke-Spolaor, S; Cameron, A D; Champion, D J; et al.
ABSTRACT: Fast radio bursts (FRBs) are millisecond pulses of radio emission of seemingly extragalactic origin. More than 50 FRBs have now been detected, with only one seen to repeat. Here we present a new FRB discovery, FRB 110214, which was detected in the high-latitude portion of the High Time Resolution Universe South survey at the Parkes telescope. FRB 110214 has one of the lowest dispersion measures of any known FRB (DM = 168.8 ± 0.5 pc cm −3 ), and was detected in two beams of the Parkes multibeam receiver. A triangulation of the burst origin on the sky identified three possible regions in the beam pattern where it may have originated, all in sidelobes of the primary detection beam. Depending on the true location of the burst the intrinsic fluence is estimated to fall in the range of 50–2000 Jy ms, making FRB 110214 one of the highest fluence FRBs detected with the Parkes telescope. No repeating pulses were seen in almost 100 h of follow-up observations with the Parkes telescope down to a limiting fluence of 0.3 Jy ms for a 2 ms pulse. Similar low DM, ultrabright FRBs may be detected in telescope sidelobes in the future, making careful modelling of multibeam instrument beam patterns of utmost importance for upcoming FRB surveys.